(untitled) (Applied Sciences in Dentistry, 2024)
Cleft lip and palate (CLP) is a common congenital defect in the craniofacial region, requiring multidisciplinary treatment and multiple surgeries. Primary and secondary alveoloplasties are performed in childhood and pre-adolescence, respectively, with tertiary alveoloplasty at growth’s end for dental rehabilitation. Oronasal fistulas are a complication post-alveoloplasty, influenced by various factors like patient age, cleft type, surgical experience, and postoperative infections. This paper presents a case of tertiary alveoloplasty using an autologous chin graft in a 52-year-old male with a history of CLP, diabetes, smoking, and previous unsuccessful surgeries. The surgery involved resecting the fistula, reconstructing the nasal floor and alveolar ridge with grafts, and achieving tension-free closure. Postoperative results showed significant bone regeneration and successful reconstruction. The case highlights the challenges in oral rehabilitation of CLP patients, considering factors like scar tissue, systemic health, and implant integration difficulties. The choice of a chin graft offered advantages over iliac crest grafts, with lower morbidity and higher success. The patient’s systemic conditions led to the decision to use a fixed plural dental prosthesis (FPP) instead of further implants. This emphasizes the need for comprehensive patient evaluation and a multidisciplinary approach in treatment planning.